THE EFFECT OF TRAINING AND WORK QUALITY ON EMPLOYEE WORK PERFORMANCE IN THE COMMODITY FUTURES LEGISLATION BUREAU, WAREHOUSE RECEIPT SYSTEM AND COMMODITY AUCTION MARKET - Hanna Herviana; Enjang Sudarman; Bambang Nurakhim (Yayasan Pendidikan Cahaya Budaya Indonesia, 2026)
This study aims to determine the effect of training and work quality on employee performance at the commodity futures legislation bureau with warehouse receipt system and commodity auction market. The phenomenon underlying this study is the discovery of employees with suboptimal work performance levels. In this study the author used quantitative research. The population in this study was 65 employees. In this study the author used the sampling technique used in this study was total sampling. With the total sampling technique, a sample of 65 employees was taken at the commodity futures legislation bureau with warehouse receipt system and commodity auction market BAPPEBTI. Data were collected using a closed questionnaire with a Likert scale, and analyzed using multiple linear regression with the help of the SPSS program version 20. The results of the study showed that partially and simultaneously, the influence of training and work quality had a positive and significant effect on work performance. This study emphasizes the importance of being able to follow up with appropriate policies in order to be able to improve work performance optimally.